Oracle BPM suite 11g developer's cookbook : over 80 advanced recipes to develop rich, interactive business processes using the Oracle Business Process Management Suite /: over 80 advanced recipes to develop rich, interactive business processes using the Oracle Business Process Management Suite. (2012) - Acharya, Vivek
No abstract available